1997
DOI: 10.1046/j.1365-3040.1997.d01-149.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ozone on the plasma membrane proteins in Arabidopsis thaliana (L.) leaves

Abstract: The protein pattern of leaf plasma membranes from Arabidopsis thaliana (L.) Landsberg erecta was analysed in order to detect changes induced by acute short‐term ozone treatment. Plasma membranes were isolated 0, 3 and 8 h after the end of a 2 h fumigation of the plants with 500 nmol mol−1 of O3. Proteins extracted from plasma membranes were separated by high‐performance two‐dimensional polyacrylamide gel electrophoresis. Eight hours after the end of fumigation, one new protein appeared and the amounts of two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Photosynthetic protein mRNAs (Conklin & Last, 1995) and polyamines (Scalet et al ., 1994) are also commonly up‐regulated by O 3 . Ozone alters the thylakoid and chloroplast membranes in turn, decreasing photosynthetic capacity (Tognini et al ., 1997) and weakening plasma membranes (Tokarska‐Schlattner et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic protein mRNAs (Conklin & Last, 1995) and polyamines (Scalet et al ., 1994) are also commonly up‐regulated by O 3 . Ozone alters the thylakoid and chloroplast membranes in turn, decreasing photosynthetic capacity (Tognini et al ., 1997) and weakening plasma membranes (Tokarska‐Schlattner et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was observed after in vivo treatment of whole tissue with SO 2 and O 3 prior to membrane isolation. Tokarska-Schlattner et al (1997) have recently reported that O 3 fumigation of Arabidopsis leaves results in an increase in some plasma membrane proteins as shown by two-dimensional gel electrophoresis. However, the sizes of these proteins do not correspond with that of the H + -ATPase.…”
Section: Discussionmentioning
confidence: 98%